1981
DOI: 10.1111/j.1399-3054.1981.tb04497.x
|View full text |Cite
|
Sign up to set email alerts
|

Soaking injury and its reversal with polyethylene glycol in relation to respiratory metabolism in high and low vigor soybean seeds

Abstract: Germination and growth of unaged (high vigor) and accelerated aged (41°C and 100% RH for 4 days; low vigor) soybean [Glycine max (L.) Merr. cv. Essex] seeds were severely reduced by soaking the seeds under water at 25°C during the first 1 to 8 h of imbibition. Soaking in 30% polyethylene glycol (PEG) did not injure high vigor seeds and improved the performance of low vigor seeds. Soaking in water increased subsequent RQ values and acetaldehyde and ethanol levels. In high vigor seeds, the increase in RQ lasted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
28
0
1

Year Published

1983
1983
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 20 publications
3
28
0
1
Order By: Relevance
“…In their study, the damage was markedly reduced by the use of an osmotic-regulating solution of polyethylene glycol (PEG 6000). They also found that the cells that failed to be stained with TTC were observed only on the periphery of the cotyledon; a similar result was reported by Woodstock and Taylorson (1981). Nordin (1984) demonstrated that the seed coat acted as a semi-permeable membrane, permitting the entry of water and certain solutes while restricting others.…”
supporting
confidence: 66%
“…In their study, the damage was markedly reduced by the use of an osmotic-regulating solution of polyethylene glycol (PEG 6000). They also found that the cells that failed to be stained with TTC were observed only on the periphery of the cotyledon; a similar result was reported by Woodstock and Taylorson (1981). Nordin (1984) demonstrated that the seed coat acted as a semi-permeable membrane, permitting the entry of water and certain solutes while restricting others.…”
supporting
confidence: 66%
“…Muramatsu et al (2008) also found that both the seed coat and the aleurone layer play a role in reducing the speed of water absorption in 'Peking'. Soybean seeds are severely damaged by water with a high osmotic potential (Woodstock and Tao, 1981;Woodstock and Taylorson, 1981;Nakayama et al, 2005). At higher temperatures, seed germination was reduced significantly by increasing duration of soaking (Hou and Thseng, 1991); the results of the present study agreed with their finding (Table 1), but further study is needed to clarify the mechanism underlying the difference in the responses to 20ºC and 25ºC among cultivars.…”
Section: Discussionmentioning
confidence: 99%
“…Leguminous seeds are known to be intolerant to water immersion (Woodstock and Taylorson, 1981). Rapid water uptake by dry seeds of soybean causes physical destruction to the cotyledons (Nakayama et al, 2004;Kokuryu et al, 2009), and injures the membranes.…”
mentioning
confidence: 99%
“…Rapid water uptake by dry seeds of soybean causes physical destruction to the cotyledons (Nakayama et al, 2004;Kokuryu et al, 2009), and injures the membranes. Anaerobic conditions force soybean seeds to change from respiration to fermentation (Woodstock and Taylorson, 1981), the latter reducing the level of energy acquisition.…”
mentioning
confidence: 99%